Principles and labs for fitness and wellness - Werner W. K Hoeger (Morton, 1997)
The content of this book serves as a guide to implement a complete lifetime fitness and wellness program. In addition to a thorough discussion on physical fitness, including all health- and skill-related components; extensive and up to date information is provided on nutrition, weight management, cardiovascular and cancer risk reduction, exercise and aging, stress management, prevention of sexually transmitted diseases, and substance abuse control ( including tobacco, alcohool, and other psychoactive drugs ).